Qathi and Zhanni’s Approaches to Understanding the Quran and Hadith: An Islamic Legal Perspective - Wahid, Sahid; Samin, Sabri; Supardin, Supardin (Journal of Universal Community Empowerment Provision, 2025)
This research explores the qathi and zhanni approaches in understanding the texts of the Qur’an and Hadith as the primary sources of Islamic law. Qathi refers to texts with definitive authenticity and meaning, while zhanni pertains to texts that are speculative or open to interpretation. The distinction between the two has significant implications in legal reasoning, particularly in determining whether a text is subject to ijtihad (independent reasoning). This study analyzes both classical and contemporary scholarly perspectives on textual authority and emphasizes the importance of reason (ijtihad) in contextualizing Islamic teachings. The findings indicate that ijtihad is essential for interpreting zhanni texts, especially in addressing evolving social issues. Therefore, a comprehensive understanding that integrates both textual analysis and contextual awareness is crucial for formulating adaptive and relevant Islamic legal thought.